"A Modern Weapon for Modern Man": Marxist Masculinity and the Social Practices of the One Big Union, 1919-1924 - McCallum, Todd (Simon Fraser University, 1995)
In March 1919, more than 230 union representatives gathered in Calgary for the Western Labor Conference. There, they initiated plans for a revolutionary industrial organizatin, the One Big Union, which embodied the internationalist principles of Marxist unionism. Within its first year, the One Big Union (OBU) issued over 70,000 membership cards, and was a powerful symbol of working-class demands for the end of class exploitation. However, given its patriarchal inheritance, the OBU was always something more than just a class organization. It was an attempt by working men to organize around a specific sense of gender identity, which I have called Marxist masculinity, in order to reconstitute the social bases of male power. The first chapter outlines the events surrounding the creation of the OBU in 1919 and the wave of general strikes that swept through Canada that summer. In particular, it sketches the relationship between class politics and a masculine structure of feeling, and how this relationship influenced the OBU's ideology. The second chapter discusses three elements around which Marxist masculinity was constructed. To begin, the experiences of women in the OBU are situated in relation to the organization's policies regarding membership in individual unions and the Women's Auxilliary. As well, it examines the personal lives of OBU leaders and the naturalized assumptions about heterosexuality which governed their politics. The final chapter discusses the purge of Tom Cassidy and Catherine Rose, two dedicated activists fired because of rumours of their sexual involvement. The OBU leadership wanted to prevent a public moral panic around issues of "free love" and was thus determined to have the matter kept quiet. In taking this position, OBU leaders regulated the gender and sexual identities of union members through concepts of proper masculine and feminine socialist behaviour.